Accounting Standards and the Value Relevance of Financial Statements - Mohamad , Shafi; Keong, Ooi Chee; Ehsanullah, Syed (Asian Journal of Empirical Research, 2019)
Using the data of 68 Malaysian listed firms, this study attempts to examine the relationship between accounting standards and the value relevance of financial statements. It also explores the difference in accounting treatment between accruals accounting and cash accounting, and evidence of supplies. This process confirmed that accruals accounting provided a more transparent picture of accounting information when compared with cash accounting aspect. Our findings are quite consistent with our hypothesis which clearly states that in economies wherein strong and secure protection mechanisms for shareholders exist, tend to apply the use of accruals accounting with confidence, assuming that the value relevance of accounting information would not be compromised at any stage.